Representation of Symbolism in Women’s Scriptions by Bulgarian, Moldavian and Ukrainian Artists - Kizevych, Anastasiia (Journal of Danubian Studies and Research, 2025)
Abstract: This article explores the symbolic representation of women in the art of Bulgarian, Moldavian, Romanian, and Ukrainian artists in Bessarabian region. Through a comparative analysis of works by artists such as O. Kara, P. Makedonskyi, M. Radulescu, and A. Baranovich the study highlights female imagery as a profound symbol of cultural identity, resilience, and continuity. Women are portrayed not merely as aesthetic subjects but as archetypal figures deeply embedded in folklore, spirituality and communal memory. The article emphasizes the convergence of national artistic traditions and the shared cultural motifs that unite Bessarabia’s diverse ethnic landscape. Symbolism emerges as a key artistic strategy, allowing artists to convey complex cultural and political narratives often challenging dominant ideological norms, such as Socialist Realism, and affirming national uniqueness. The study also illustrates how personal histories, everyday life, and ancestral memory are encoded in depicting women, positioning them as individual and collective icons. By analyzing these artistic representations, the article contributes to the understanding of gender, symbolism, and national identity in Eastern European art while shedding light on the broader role of visual culture in saving and transmitting heritage across generations